SAR study of bisamides as cyclophilin a inhibitors for the development of host-targeting therapy for hepatitis C virus infection. Issue 19 (1st October 2020) - Li, Xiaoli; Han, Jinhe; Lee, Hye Won; Yoon, Yi-Seul; Jin, Yifeng; Khadka, Daulat B.; Yang, Suhui; Kim, Meehyein; Cho, Won-Jea
Graphical abstract: Highlights: A total of 12 bisamide compounds were designed and synthesized to test anti-HCV activity and cytotoxicity. The EC50 and CC50 values of the bisamide compounds were evaluated to identify the potent compounds. Western blot analysis revealed that 7c and 7j inhibited viral protein expression in a dose-dependent manner. Molecular docking studies demonstrated that 7c is positioned in CypA active site. The SPR results of 7b (KD = 4.60 ± 0.05 μM) revealed that bisamide derivatives bind to CypA. Abstract: The therapy of chronic hepatitis C virus infections has significantly improved with the development of direct-acting antivirals (DAAs), which contain NS3/4A protease, NS5A, and NS5B polymerase inhibitors. However, mutations in specific residues in these viral target genes are associated with resistance to the DAAs. Especially inhibitors of NS3/4A protease and NS5A, such as grazoprevir and velpatasvir, have a low barrier to resistant mutations. As a result, the mutations influence the virological outcomes after DAA treatment. CypA inhibitors, as host-targeted agents, act on host factors to inhibit HCV replication, exhibiting a high resistance barrier and pan-genotype activities against HCV. Therefore, they can be developed into alternative, more effective anti-HCV agents. However, CypA inhibitors are natural products and analogs. Based on previous studies, bisamide derivatives were designed and synthesized to develop a novel class of CypA inhibitors. Bisamide derivative 7c is a promising compound with potent anti-HCV activity at subtoxic concentrations. Surface plasmon resonance experiments revealed that 7c directly binds to CypA. All these studies indicated that the derivative 7c is a potent CypA inhibitor, which can be used as a host-targeted agent in combination with other antiviral agents for anti-HCV treatment.